2020
DOI: 10.2196/13424
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Media Use and Engagement Among Dermatology Patients to Inform Dermatological Prevention and Care in Vietnam: Cross-sectional Study

Abstract: Background Social media has emerged as a common source of dermatological information. Monitoring the patterns of social media use and engagement is important to counteract the limitations of social media. However, evidence in Vietnamese dermatology patients is lacking. Objective This study aimed to explore social media use and engagement by dermatology patients and to identify factors associated with social media use and engagement. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A 2020 cross-sectional study sought to analyze social media use amongst dermatology patients with various skin conditions. Of the 399 dermatology patients active on social media, 95.2% reported searching for, sharing, or consuming dermatology or cosmetology-related information on a social media platform, demonstrating that dermatology patients are actively searching for health information via social media platforms [ 7 ]. When social media is utilized, it can be a superior option to traditional methods.…”
Section: Social Media For Clinical Trial Enrollmentmentioning
confidence: 99%
“…A 2020 cross-sectional study sought to analyze social media use amongst dermatology patients with various skin conditions. Of the 399 dermatology patients active on social media, 95.2% reported searching for, sharing, or consuming dermatology or cosmetology-related information on a social media platform, demonstrating that dermatology patients are actively searching for health information via social media platforms [ 7 ]. When social media is utilized, it can be a superior option to traditional methods.…”
Section: Social Media For Clinical Trial Enrollmentmentioning
confidence: 99%
“…This health care social media platform provides an interactive way to communicate, as users can participate in questionnaires and short polls about psoriasis and the ways it is affecting their lives. Patients with psoriasis are often stigmatized due to the high visibility of the disease; therefore, searching for information over the internet and taking advantage of the anonymity provided might be beneficial [ 3 , 4 ]. Through Myderma, patients could also look for a nearby dermatologist, simply by clicking on the “Find Dermatologist” icon, which leads to the Hellenic Society of Dermatology and Venereology, with call-to-action requests.…”
mentioning
confidence: 99%
“…Despite significant progress over the last decades, psoriasis is still associated with increased stigmatization, accompanied by significant psychosocial burden, especially for women [ 4 ]. This was reflected by the increased prevalence of female users of the website and Facebook.…”
mentioning
confidence: 99%
“…The most common motivation is to have a better understanding of a disease, while the others are to self-diagnose and research alternative therapy [15]. Interestingly, in a different study conducted in Vietnam, it was concluded that social media use is high among dermatology patients, but there was only a moderate utilization of social media as a source of dermatology-related information [28].…”
mentioning
confidence: 99%